2016
DOI: 10.1542/peds.2016-1640
|View full text |Cite
|
Sign up to set email alerts
|

Third Trimester Brain Growth in Preterm Infants Compared With In Utero Healthy Fetuses

Abstract: BACKGROUND AND OBJECTIVES:Compared with term infants, preterm infants have impaired brain development at term-equivalent age, even in the absence of structural brain injury. However, details regarding the onset and progression of impaired preterm brain development over the third trimester are unknown. Our primary objective was to compare third-trimester brain volumes and brain growth trajectories in ex utero preterm infants without structural brain injury and in healthy in utero fetuses. As a secondary objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(81 citation statements)
references
References 75 publications
1
73
0
1
Order By: Relevance
“…18 Growth of the BPD between 7 and 27 days was slower (1.30 mm/week PNA) than after the first 27 days (2.17 mm/week PNA), from which time postnatal growth of the BPD approximates to expected fetal growth (2.10 mm/week PMA) as reported from cross-sectional data by Kurmanavicius et al 19 Higher GA at birth related to slower growth of the BPD from birth to TEA, in keeping with normative data for fetal growth of the BPD that demonstrates a slowing of growth with increasing PMA. 19,20 However, infants born at Ͻ30 weeks' GA have smaller brains at TEA than term-born controls, and most are likely to have slower rates of brain growth immediately after birth than normally expected in utero. 20,21 In the current study, CCL growth was relatively constant from birth to 27 days' PNA but slowed by half thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Growth of the BPD between 7 and 27 days was slower (1.30 mm/week PNA) than after the first 27 days (2.17 mm/week PNA), from which time postnatal growth of the BPD approximates to expected fetal growth (2.10 mm/week PMA) as reported from cross-sectional data by Kurmanavicius et al 19 Higher GA at birth related to slower growth of the BPD from birth to TEA, in keeping with normative data for fetal growth of the BPD that demonstrates a slowing of growth with increasing PMA. 19,20 However, infants born at Ͻ30 weeks' GA have smaller brains at TEA than term-born controls, and most are likely to have slower rates of brain growth immediately after birth than normally expected in utero. 20,21 In the current study, CCL growth was relatively constant from birth to 27 days' PNA but slowed by half thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, infants born at Ͻ30 weeks' GA have smaller brains at TEA than term-born controls, and most are likely to have slower rates of brain growth immediately after birth than normally expected in utero. 20,21 In the current study, CCL growth was relatively constant from birth to 27 days' PNA but slowed by half thereafter. Similarly, Anderson et al 9 showed that postnatal growth of the CCL in verylow-birth-weight infants approximated fetal growth (1.4 -1.89 mm/week PMA) within the first 2 postnatal weeks but subsequently slowed to approximately half of that expected.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the lack of reviews for preterm infants, the need to study this population in relation to breast milk and maternal medication should be emphasized. Breast milk is particularly beneficial to preterm infants in providing appropriate nutrition during their time growing ex‐utero in a crucial period of accumulating nutrient reserves typical for the developing fetus (Bouyssi‐Kobar et al, ; Carlson & Ziegler, ; Ehrenkranz et al, ) and reducing necrotizing enterocolitis and sepsis, which is more prevalent in this population (Underwood, ). Further attention to preterm infants is also warranted because they are more vulnerable than term infants to toxicity from drug exposure through breast milk.…”
Section: Introductionmentioning
confidence: 99%
“…(3) MRI studies in preterm infants have shown reduced brain volumes associated with intraventricular hemorrhage, bronchopulmonary dysplasia and postnatal dexamethasone exposure. (46) Even among preterm infants without clear clinical risk factors, reductions in tissue volumes and brain growth have been demonstrated, (79) some of which may be related to the rapid brain development occurring ex-utero during the period corresponding to the third trimester. (10, 11) Despite providing valuable insight into brain growth trajectories in preterm infants, the majority of these studies have been cross-sectional MRI investigations at term-equivalent postmenstrual age (PMA).…”
Section: Introductionmentioning
confidence: 99%
“…(7) Importantly, longitudinal MRI data can provide insight into critical time-points of brain maturation and tissue-specific vulnerability, helping contextualize trajectories of brain development in relation to clinical and environmental exposures. (13) Studies of infants born at varying gestational ages have shown dramatic linear increases in global and regional brain volumes from 25 to 40 weeks’ gestation.…”
Section: Introductionmentioning
confidence: 99%